INTERAKSI SOSIAL DAN TINGKAT PENDAPATAN NELAYAN PURSE SEINE DI DESA LATUHALAT KECAMATAN NUSANIWE KOTA AMBON - Costantinus Sahanaya; Costansa Glory Lessil; Anthonio Johan Latuihamallo (JURNAL BADATI, 2023)
Social interaction and income level of Purse Seine fishermen in Latuhalat village, Nusaniwe sub-district, Ambon City, is a study that aims to describe the form of social interaction of the Purse Sain fishing community and analyze the income of both the business, the owner and the income of the crew. The method used in this research is the method descriptive, to analyze data on the form of social interaction of purse fisherman, qualitative analysis methods are used, while fishermen's income is used, fishermen's income uses quantitative analysis methods. The research results show that the social interactions of Purse Seine fishermen in Latuhalat village consist of cooperation, competition, and disputes or conflicts. The average business income during the fishing season (MI) is IDR 6,086,651, the average owner's income is IDR 2,434,661, the average crew income is IDR 2,434,661, while the average FAD income is IDR 1,217.